Information law relations on the Internet: theoretical basis - Sukhaparau, Viktar P. (Journal of the Belarusian State University. Law, 2021)
The features of information law relations as social relations regulated by information law are revealed in the article. Special attention is paid to scientific approaches to the degree of independence of information law relations on the Internet. Basing on the analysis of features and definitions of information law relations, the characteristics of information law relations developing on the Internet are given as well as their features are disclosed on the basis of a list of relevant participants and objects of information law regulation.